Recommended primary outcomes for clinical trials evaluating hemostatic agents in patients with intracranial hemorrhage: a consensus statement - Mayer, Stephan A.; Frontera, Jennifer A.; Jankowitz, Brian; Kellner, Christopher P.; Kuppermann, Nathan; Naik, Bhiken I.; Nishijima, Daniel K.; Steiner, Thorsten; Goldstein, Joshua N. (JAMA network open, 2021)
In patients with acute spontaneous or traumatic intracranial hemorrhage, early hemostasis is thought to be critical to minimize ongoing bleeding. However, research evaluating hemostatic therapies has been hampered by a lack of standardized clinical trial outcome measures.To identify appropriate primary outcomes for phase 2 and 3 clinical trials of therapies aimed at reducing acute intracranial bleeding.A comprehensive review of all previous clinical trials of hemostatic therapy for intracranial bleeding was performed, and studies measuring the frequency, risk factors, and association of intracranial bleeding with outcome of hemorrhage growth were included.A hierarchy of 3 outcome measures is recommended, with the first choice being a global patient-centered clinical outcome scale measured 30 to 180 days after the event; the second, a combined clinical and radiographic end point associating hemorrhage expansion with a poor patient-centered outcome at 24 hours or later; and the third, a radiographic measure of hemorrhage expansion at 24 hours alone. Additional recommendations stress the importance of separating various subtypes of bleeding when possible, early treatment within a standardized treatment window, and the routine use of computerized planimetry comparing continuous measures of absolute and relative hemorrhage growth as either a primary or secondary end point.Standardization of outcome measures in studies of intracranial bleeding and hemostatic therapy will support comparative effectiveness research and meta-analysis, with the goal of accelerating the translation of research into clinical practice. The 3 outcome measures proposed in this consensus statement could help this process.